Code-to-Code Comparison for a PbLi Mixed-Convection MHD Flow. (3rd July 2020) - Smolentsev, S.; Rhodes, T.; Yan, Y.; Tassone, A.; Mistrangelo, C.; Bühler, L.; Urgorri, F. R.
Abstract: In "An Approach to Verification and Validation of MHD Codes for Fusion Applications" [S. Smolentsev et al., Fusion Eng. Des., Vol. 100, p. 65 (2015)], an effort for verification and validation of computer codes for liquid metal flows in a magnetic field for fusion cooling/breeding applications was initiated. The current study continues that effort. A group of experts in computational magnetohydrodynamics from several institutions in the United States and Europe performed a code-to-code comparison for the selected reference case of a mixed-convection buoyancy-opposed magnetohydrodynamic flow of eutectic lead-lithium (PbLi) alloy in a thin-wall conducting square duct at Hartmann number Ha = 220, Reynolds number Re = 3040, and Grashof number Gr = 2.88 × 10 7 . As shown, the reference flow demonstrates a boundary layer separation in the heated region and formation of a reversed flow zone. The results of the comparison suggest that all five solvers predict well the key flow features but have moderate quantitative differences, in particular, in the location of the separation point. Also, two of the codes are more computationally dissipative, showing no velocity and temperature oscillations.